Cultura surda e transculturalidade : a questão das identidades numa comunidade acadêmica da Grande Vitória - Bandeira, Adriana Gomes (2018)
This research aims to think responsively and responsibly how the deaf subjects of the Grande Vitória about the terms deaf culture and deaf identity in their discourses. Through the discussion of cultural studies, the deaf community sought to transform the view of the deaf subject, traditionally conceived by the bias of medicine, assistance, disability and lack of hearing, to a cultural bias, the critical subject, with their own identities and language, that is, deaf identities and sign language. Through these studies the Deaf Studies are created, with the aim of fomenting new concepts and ideas about the deaf person. As a proposal for development in these studies, we seek the idea of transculturality to increase this research and bring new cultural perspectives in view of the fact that there are still so many episodes of intolerance and hatred among people. The idea of a closed, superior culture that divides between "us" and "them" often ends up producing more segregation and prejudice. Therefore, the purpose of our research is to think deaf culture through transculturality, dialogism, listening to the other, and also to rethink the concepts of deaf identities and culture, in order to contribute to the construction of a more tolerant and receptive society to the other. The corpus of this research is formed by interviews with representatives of the deaf community of Grande Vitória that are inserted in the academic community on issues such as: deaf identity and deaf culture, which are terms commonly used / researched by scholars of the Deaf Studies. The hypothesis is that the deaf community has assumed a closed position in the concepts of culture and deaf identity. To analyze if this hypothesis is supported, we use a dialogic methodology of listening with the pretension of understanding the voices that pass through the subjects involved in this research process.